Chemically conjugated sophorolipids on CdTe QDs: a biocompatible photoluminescence nanocomposite for theranostic applications - Singh, Pooja; Joshi, Kasturi; Guin, Debanjan; Prabhune, Asmita (RSC Advances, 2013)
Functional nontoxic cadmium telluride (CdTe) quantum dots (QDs) have been synthesized using a natural functional glycolipid belonging to the family of sophorolipids (SL) as a surface-modifying agent. These SLs with open acidic form are highly suitable for QDs stabilization, are readily obtained by a fermentation process of the yeast Candida bombicola (polymorph Starmerella bombicola) in large amounts. In this work chemically stable, water soluble, and photoluminescent CdTe QDs were successfully conjugated to sophorolipids via a cross-linking reaction. The formation of SLs conjugated CdTe QDs was confirmed using different analytical techniques X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), Electron Diffraction (ED), Atomic Force Microscopy (AFM), Dynamic Light Scattering (DLS), and Photoluminescence (PL). It was shown that after being conjugated with SL the SL-CdTe QDs becomes biocompatible, still maintaining its water solubility and photoluminescence properties. The final SL coated photoluminescent CdTe QDs represent interesting biocompatible materials potentially useful for biomedical applications.

Glucose oxidase conjugated H2O2 sensitive CdTe QDs: an effective fluorescence tool for glucose sensing - Singh, Pooja; Prabhune, Asmita; Ogale, Satishchandra B.; Guin, Debanjan (Journal of Materials Chemistry B, 2013)
Water-soluble quantum dots (QDs) are extensively used for molecular sensing because of the flexibility they offer in terms of modification of the QDs surface with a variety of functional groups using thiol chemistry and monitoring by fluorescence intensity. We describe a simple assay that allows the photoluminescence (PL) detection of H2O2 and glucose in aqueous samples and demonstrate its applicability by estimating glucose in blood. To enable the glucose detection, we functionalized the 3-mercaptopropanoic acid (MPA) capped CdTe QDs with glucose oxidase (GOx), the enzyme specific to b-D-glucose, using carbodiimide chemistry. The fluorescence of the GOx-functionalized CdTe QDs was quenched on the interaction with glucose. The same photoluminescence quenching was also observed in gel form, when a GOx modified CdTe QDs loaded agarose gel was dipped in H2O2 and glucose solutions, respectively.

Evaluation of n-type ternary metal oxide NiMn2O4 nanomaterial for humidity sensing - Gawli, Yogesh; Badadhe, Satish S.; Basu, Aniruddha; Guin, Debanjan; Shelke, Manjusha V.; Ogale, Satishchandra (Sensors and Actuators B-Chemical, 2014)
Synthesis of mono-dispersed oleic acid (OA) capped NiMn2O4 (NMO) nanoparticles and their use for humidity sensing is reported. Oleic acid capped NMO (NMO-cOA) nanoparticles are synthesized from nickel oleate and manganese oleate complex. NiMn2O4 is obtained by removing oleic acid capping at 500 degrees C in air. X-ray diffraction analysis shows formation of pure NiMn2O4 phase which is also confirmed by HRTEM-SAED analysis. The TEM analysis also shows that the nanoparticles are nearly mono-dispersed. Doctor bladed films of NMO nanoparticles are seen to exhibit excellent humidity sensing property. The resistivity is seen to change by two orders with humidity change from 11% RH to 92% RH with fairly good linearity over the entire range. The response and recovery times are also fast. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Humidity; Impedance; Nanoparticles; NiMn2O4; Oleic acid; Sensor

Large scale synthesis of graphene quantum dots (GQDs) from waste biomass and their use as an efficient and selective photoluminescence on-off-on probe for Ag+ ions - Suryawanshi, Anil; Biswal, Mandakini; Mhamane, Dattakumar; Gokhale, Rohan; Patil, Shankar; Guin, Debanjan; Ogale, Satishchandra (Nanoscale, 2014)
Graphene quantum dots (GQDs) are synthesized from bio-waste and are further modified to produce amine-terminated GQDs (Am-GQDs) which have higher dispersibility and photoluminescence intensity than those of GQDs. A strong fluorescence quenching of Am-GQDs (switch-off) is observed for a number of metal ions, but only for the Ag+ ions is the original fluorescence regenerated (switch-on) upon addition of L-cysteine.

Starch (Tapioca) to carbon dots: an efficient green approach to an on-off-on photoluminescence probe for fluoride ion sensing - Basu, Aniruddha; Suryawanshi, Anil; Kumawat, Begraj; Dandia, Anshu; Guin, Debanjan; Ogale, Satishchandra B. (Analyst, 2015)
Photoluminescent carbon dots of 4-5 nm size were prepared from starch (Tapioca Sago) through a solution method under mild conditions. The as-prepared carbon dots were used as photoluminescence probes for highly anion selective fluoride ion detection in aqueous solutions. A ready-to-use device is also demonstrated.